Bandrés, a fair fight for freedom - Margenat, SJ, José María (Razón y fe, 2012)
The lawyer Juan María Bandrés Molet (1932-2011), jurist and politician, founder of Euskadiko Ezkerra, can and should be considered one of the personalities who have contributed the most to the cause of peace and freedom in the Basque Country and in Spain. In this note-tribute, some of the defining factors of the pacifist Bandrés are unraveled: his humanism, his deep sense of loyalty and freedom, his commitment to peace policies and his deep-rooted Christian sense of life and history.